Manajemen Pembiayaan Pendidikan di Sekolah Dasar Kecamatan Ngaliyan Kota Semarang (Studi Kasus di Sekolah Dasar Negeri Tambakaji 04) (Educational Management, 2022)
The purpose of this study is to describe and analyze the RAPBS (School Revenue and Expenditure Budget Plan) including the source of funds originating from BOS (School Operational Assistance). This study uses a qualitative design, taking full advantage of the ways of interpretation by presenting it in the form of a description. The sampling technique in this study used a purposive sampling technique. Methods of data collection in this study use interview techniques, observation, and documentary studies. The results of the study indicate that the principal has placed a team in the management of education funds. Education funds are managed in a flexible, accountable, and transparent manner according to procedures. In the initial stage, the team carried out financial planning by compiling a list of items to be spent. At the stage of implementing the financing of goods, the team made transactions through a non-cash system, so that all funds were in the school's account and could only be used according to the approved budget plan. In the supervision process, the realization of the RAPBS is supervised by officials. Finally, as a form of accountability for financial management, the team printed several accounting reports documents.